Lazo de control y monitoreo para la temperatura del aire de carga en las unidades allen ps1 de la empresa Sierracol Energy Arauca LLC - Díaz Romero, Oscar Mauricio (Universidad Antonio Nariño, 2021)
The degree work is oriented towards the design of a control loop to guarantee the stable and reliable control of the charge air temperature variable, in the Allen units in the PS1 Caño Limón Arauca pumping station, of the SIERRACOL ENERGY company. ARAUCA LLC and thus maintain the ideal engine inlet temperature to meet the manufacturer's recommendations regarding temperature, which should be maintained at 120 ° F. Currently, the Micronik 200 controller is installed; it was installed 20 years ago and currently does not offer reliable temperature control due to faults unexpected events that cause the bypass valve to open 100% generating an increase in the charge air temperature and generating sudden trips of the unit when 140 ° F is reached.